STRATEGIES FOR DISSEMINATING IMMIGRATION INFORMATION AT THE CLASS I IMMIGRATION OFFICE OF TPI BENGKULU - Rasona S Akbar; Intan Nurkumalawati; Mizan Tri Rahmawan (Polteknik Imigrasi, 2021)
Based on the cultural factors of the people who prefer audio-visual rather than typography, and the majority of people already have smartphones making it easier to access information through social media, based on this phenomenon, the Immigration Office requires to implement new ideas in packaging immigration information using short films. This study aims to determine the strategy of disseminating immigration information using short films and the public's response to the strategy. The reason for doing this research is that researchers are interested in the strategy of disseminating information using short films because apart from being able to provide entertainment to the public, they also provide education on Immigration information. This type of research is a qualitative research with a descriptive analysis approach. The object of this research is the Functionary of Immigration Office Class I TPI Bengkulu and the people of Bengkulu Province. The results of interviews in this study show that the society prefers information that uses audio visuals rather than typography. The target in this strategy is people aged 18 years and over or already have an ID card. The content of the message conveyed is presented with light subjet so that it is easily understood by the public. By adopting local wisdom the use of regional languages in short films to attract attention and make it easier for the public to understand the message of the short film. The media used are also those that are familiar with the community, namely Instagram and YouTube. This is evidenced by the public response that the use of the short film is appropriate.